Kesenjangan Praktik Asesmen Multiliterasi (Baca-Tulis, Numerasi, Sains, dan Digital): Studi Kasus di Kelas IV SD Negeri Tapakrejo 01 Blitar - Nunik Setyowati; Intan Sari Rufiana; Sri Rahayuningsih (Journal of Practice Learning and Educational Development, 2026)
21st-century learning demands the development of multiliteracy that encompasses reading-writing, numeracy, science, and digital literacy in a balanced manner. This study aims to: (1) describe multiliteracy assessment practices across each dimension; (2) identify the gaps between ideal assessment practices and actual field practices; and (3) analyze the contributing factors to these gaps. This research employed a qualitative approach with a case study design. The subjects were the fourth-grade teacher and representatives of fourth-grade students at SD Negeri Tapakrejo 01 Blitar. Data collection techniques included passive participant observation, semi-structured in-depth interviews, and documentation. The results indicate that multiliteracy assessment practices are highly uneven across dimensions. In reading-writing and numeracy literacy, assessments have been conducted but remain simplistic, portfolios are not yet used, and feedback is not individualized. In science literacy, assessments are conducted informally without rubrics or anecdotal records. In digital literacy, assessments are almost never explicitly performed due to limited facilities and teacher unpreparedness. The contributing factors include internal factors (limited knowledge, belief in the efficiency of written tests, and inadequate technical skills) and external factors (limited digital facilities, unsupportive school policies, and a lack of ongoing mentoring and training). Thus, it can be concluded that a significant gap exists between ideal multiliteracy assessment practices and actual practices at SD Negeri Tapakrejo 01 Blitar, particularly in science and digital literacy.